European Integration at the Crossroads: A Review Essay on the 50th Anniversary of Bela Balassa'sTheory of Economic Integration - Sapir, André (Journal of Economic Literature, 2011)
Bela Balassa's Theory of Economic Integration, published fifty years ago, is a remarkable, yet little known book. This essay reviews developments in the economic literature and in the process of European integration since the book's publication, showing that it was incredibly prescient. It anticipated by more than twenty years the modern literature on economic integration that emphasizes scale economies, imperfect competition, and economic geography. It also predicted that monetary union cannot function properly without political unification, a condition well illustrated by the recent euro-debt crisis that is likely to be a watershed in the history of European integration. (JEL B31, F15, F36, G01)